Movement of the palanquin through the streets - Mumbai Archive Project Team (Jio Institute, 2024)
The route taken by the palki includes temples, homes of devotees, and public spaces, symbolizing the spread of divine blessings across the community. The movement of the palanquin through the streets represents the journey of the deity, blessing the areas and people it passes by. This journey is symbolic of the divine's omnipresence and its accessibility to devotees.